A New Canterbury Tale - Grandillo, Tanya Sue (Cornfield Review, 2015)
A new character added to the classic story of the Canterbury Tales by Chaucer. The members of the traveling band must tell a tale to pass the time and win the bet. Remember during the medievel times being a nun was not always a virtuous engagement.